2022
DOI: 10.1186/s13054-022-04005-0
|View full text |Cite
|
Sign up to set email alerts
|

TTCOV19: timing of tracheotomy in SARS-CoV-2-infected patients: a multicentre, single-blinded, randomized, controlled trial

Abstract: Background Critically ill COVID-19 patients may develop acute respiratory distress syndrome and the need for respiratory support, including mechanical ventilation in the intensive care unit. Previous observational studies have suggested early tracheotomy to be advantageous. The aim of this parallel, multicentre, single-blinded, randomized controlled trial was to evaluate the optimal timing of tracheotomy. Methods SARS-CoV-2-infected patients within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…There was a statistically signi cant shortening of the early tracheotomy group for the late tracheotomy group in terms of length of hospitalization, ICU stay, IMV time, and sedation time. Many previous studies have produced similar results[6, 24,25]. This is probably related to the fact that tracheotomy increases patient comfort and reduces the need for sedation [26].…”
Section: Discussionsupporting
confidence: 54%
“…There was a statistically signi cant shortening of the early tracheotomy group for the late tracheotomy group in terms of length of hospitalization, ICU stay, IMV time, and sedation time. Many previous studies have produced similar results[6, 24,25]. This is probably related to the fact that tracheotomy increases patient comfort and reduces the need for sedation [26].…”
Section: Discussionsupporting
confidence: 54%
“…409 articles were excluded due to duplication. Eventually, 21 RCTs [ 5 , 10 , 20 38 ] involving 3621 patients were enrolled for this meta-analysis. The flow diagram of the literature search and study selection is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The interventions were not delivered mostly due to rapid improvement in the condition, in both the early and late tracheostomy groups. These results, together with the data presented by Villemure-Poliquin et al (5), suggest that it is unlikely to be able to observe a significant signal for beneficial effect of early tracheostomies performed within the first 10 days of mechanical ventilation in patients whose respiratory support is primarily due to nonneurologic cause (14). It is perhaps pertinent to invest time and effort into the implementation of better sedation and weaning practices and allow patients more time to be liberated from mechanical ventilation utilizing conventional endotracheal intubation, before an invasive procedure is performed on the ICU.…”
mentioning
confidence: 85%
“…The study was stopped early on the recommendation of the data safety monitoring board and due to the reduction inpatient numbers. Less than half of the 150 randomized patients have actually received the intervention, and the intention to treat analysis did not show any difference between the two groups with regard to length of mechanical ventilation or other secondary outcomes (14). The interventions were not delivered mostly due to rapid improvement in the condition, in both the early and late tracheostomy groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation